A Descriptive Analysis of Patient Safety at Universitas Gadjah Mada Academic Hospital Yogyakarta : A Case Study Using IHI Global Trigger Tool for Measuring Adverse Events - Novi Zain Alfajri; Domas Fitria Widyasari; Ratna Dewi Puspita (Academic Hospital Journal, 2018)
Background: Management of medical treatment is a very complex multi-disciplinary process with many stages. During patient care at Universitas Gadjah Mada Academic Hospital (UGM Academic Hospital) incidents involving patient safety either go unreported or are accidentally found. According to some public health research only about 10-20% of incidents were reported. The purpose of this research aimed to provide data to the management about the level of patient safety and make recommendations to improve service quality, especially to reduce injury and increase patient safety.Methods: Our study was conducted by doing a review of patient medical records of hospitalized adults (n = 60) treated in September 2015 to detect trigger and adverse events using the IHI Global Trigger Tool for Measuring Adverse Events. Group Cares was designed to reflect the adverse events that occurred anywhere in UGM Academic Hopitaltal so that all samples should be reviewed by both modules. All three remaining modules were used if necessary depending on the unit where patients were treated. Technical analysis used in this research was descriptive statistics.Results: The study found 69 incidents / triggers that occurred in 27 patients (n = 60) consisting of 47 incidents in the treatment group, 16 incidents in the surgery group, one incident in intensive care, and 5 incidents at the Emergency Department. Based on the level of injury, the incidents which happened demanded extended day care, requiring more intervention and assistance of disability. No cases of death were reported due to the incidents.Conclusions: The incidence found in all categories according to the modules with the highest incidence was the incidence of treatment and the smallest was in intensive care. Most incidents resulted in extending the duration of treatment and require more intervention. No fatal cases were reported to have resulted in the studied sample.